Potensi Tepung Beras Kaya Pati Resisten Sebagai Bahan Pangan Inovatif - Zalniati Fonna Rozali (JURNAL PANGAN, 2018)
ABSTRACTChanges in lifestyle cause people to demand the availability of functional foods that are ready to eat, nutritious and positive for health as a part of the daily menu. A food ingredient can be said to be functional if it contains components (both nutritional and non-nutritional) which have beneficial physiological effects on the functions of organs in the body. The biological role of resistant starch as an ingredient of functional food is related to the ecology of "good" microbes that live in the large intestine (colon). The use of rice flour as a source of resistant starch is an innovation to utilize broken rice, which can be applied by industries with a wide range of businesses. Modification of rice flour to increase levels of resistant starch can be done physically, chemically, enzymatically or in combination. Each of these production processes will affect the characteristics of the hospital produced. Based on the production process, characteristics, functional values, and alternative uses, rice flour rich in resistant starch has considerable potential to be developed as a functional food product for health.